Correlação de fatores clínicos e prognósticos, com a expressão da proteína p53, no carcinoma invasor de colo uterino - Schaffer, Lúcia Teresa Hinojosa; Traimam, Paulo [UNESP]; Uemura, Gilberto [UNESP]; Nahas Neto, Jorge; Nahas, Eliana Aguiar Petri [UNESP]; Pontes, Anaglória [UNESP] (My University, 2012)
The analysis of p53 protein in cervical carcinoma correlated with clinical and prognostic factors was performed in a retrospective study with p53 expression detection by immunohistochemical technique. 120 slides of patients with squamous cell cancer at the Gynecologic Oncology Clinic and stored in the Department of Pathological Anatom at the School of Medicine of Botucatu were used. Age, ethnicity, parity, smoking habit, oral contraceptive use, age at first intercourse, histology, stage, treatment, and follow-up were the cofactors associated with p53 positivity. Fisher’s exact tests were carried out to analyze associations between p53 and variables, with p < 0.05 as the significant level. The study revealed a 43.3% frequency of patients with stage II disease and p53 positive rate with p = 0.001, and 64.2% frequency with p = 0.024 of patients whose first intercourse occurred between the ages of 15 and 20. These findings show the correlation between stage II disease and age at fir st intercourse with p53 positive in invasive cervical cancer. Fisher's exact test revelead these cofactors to be statistically significant and there was no association between the protein p53 with others prognostic and analyzed cofactors. The prognostic value of p53 in cervical cancer had been examined, with the conclusion that p53 is correlated to unfavorable prognosis.

A Análise da proteína p53 no carcinoma invasor de colo uterino correlacionada a fatores clínicos e prognósticos foi realizada em estudo retrospectivo, com detecção da expressão da p53 através da técnica imunoistoquímica. Foram utilizadas 120 lâminas de pacientes do Ambulatório de Oncologia Ginecológica, diagnosticadas como carcinoma epidermóide invasor do colo uterino, arquivadas no Departamento de Anatomia Patológica da Faculdade de Medicina de Botucatu. Os co-fatores: idade, etnia, paridade, tabagismo, uso de contraceptivo oral, idade da coitarca, histologia, estadio, tratamento e seguimento foram associados à positividade da p53. Testes de Fisher foram realizados na análise de associações entre p53 e as variáveis, sendo considerado significativo o p < 0,05. O estudo revelou uma frequência de 43,3% de pacientes no estádio II da doença, cujos tumores p53 positivos tinham p = 0,001 e a frequência de 64,2%, com p = 0,024 em pacientes com idade da coitarca entre 15 e 20 anos. Os dados obtidos permitem associar o estádio II da doença e a idade da coitarca com a expressão positiva da proteína p53 no câncer de colo uterino invasor. Esses co-fatores mostraram-se estatisticamente significativos pelo teste exato de Fisher e não houve associação da proteína com outros co-fatores analisados e prognósticos. O valor prognóstico da p53 em câncer cervical tem sido examinado concluindo-se que a p53 está associada a prognóstico desfavorável.
Correlation of clinical and prognostic factors, whit the p53 protein expression in invasive cervical carcinoma
Keywords: Uterine cervical neoplasms; Genes, p53; Genes; Tumor suppressor histochemistry; Neoplasias do colo do útero; Genes p53; Genes supressores de tumor; Histoquímica